Integrated reporting: how JSE listed companies are meeting the corporate reporting transitional challenge in South Africa - Gina, Kelebogile (My University, 2014)
Integrated reporting is a relatively new phenomenon in corporate reporting which is expected to address the gap between sustainability reporting and financial reporting. The King Code of Governance for South Africa 2009 (King III) recommends that a company’s sustainability report and financial report should be integrated. JSE listed companies are required to either comply with the recommendations of King III or explain why there are not complying. The objective of the study was to identify how JSE listed companies apply the IIRC guiding principles of connectivity of information and conciseness, materiality and reliability in a manner which elucidates the link between the environmental, social and governance (ESG) performance and financial performance in their integrated report. Fourteen in-depth interviews were conducted with a mix of experts in integrated reporting and preparers of integrated reports. The results reveal that most preparers of integrated reports find connectivity of information to be the more challenging of the two principles to apply. Experts in integrated reporting suggest that the key reason for this difficulty is that the underlying decision-making processes within companies are not yet integrated because companies are still operating in silos. It then becomes difficult to force an integrated report onto a process that is not integrated. There was consensus among the respondents that an integrated report should have a strong focus on material issues in order to ensure that the report is concise. Furthermore, the information contained in the integrated report should be reliable. There was general concern over the reliability of non-financial data due to a lack of robust data gathering, processing and monitoring systems over nonfinancial information. Lastly, most respondents agreed that the Board should consider both material financial and non-financial factors when making decisions.
MBA thesis
Keywords: Corporate reporting; Integrated reporting